Species of the genus Cestrotus Loew from China (Diptera: Lauxaniidae) - Li, Shi; Yang, Ding; Gaimari, Stephen D. (Zootaxa, 2009)
The Chinese fauna of the genus Cestrotus Loew (Diptera: Lauxaniidae) is revised, including the five new species Cestrotus acuticurvus sp. nov., Cestrotus heteropterus sp. nov., Cestrotus liui sp. nov., Cestrotus longinudus sp. nov. and Cestrotus obtusus sp.nov., and the two previously described species Cestrotus apicalis (Hendel) and Cestrotus flavoscutellatus de Meijere. Extralimital records are also given for Cestrotus flavoscutellatus and Cestrotus heteropterus, including paratypes of the latter species from Thailand. A key to the species of Cestrotus from China is presented, and a list of all described species of Cestrotus is provided, with information on type locality, primary type specimen(s) and depository, synonymy, and distribution.